Spiclypeus shipporum gen. et sp. nov., a Boldly Audacious New Chasmosaurine Ceratopsid (Dinosauria: Ornithischia) from the Judith River Formation (Upper Cretaceous: Campanian) of Montana, USA. - Jordan C Mallon; Christopher J Ott; Peter L Larson; Edward M Iuliano; David C Evans (PLoS ONE)
This study reports on a new ceratopsid, Spiclypeus shipporum gen et sp. nov., from the lower Coal Ridge Member of the Judith River Formation in Montana, USA, which dates to ~76 Ma (upper Campanian). The species is distinguished by rugose dorsal contacts on the premaxillae for the nasals, laterally projecting postorbital horncores, fully fused and anteriorly curled P1 and P2 epiparietals, and a posterodorsally projecting P3 epiparietal. The holotype specimen is also notable for its pathological left squamosal and humerus, which show varied signs of osteomyelitis and osteoarthritis. Although the postorbital horncores of Spiclypeus closely resemble those of the contemporaneous 'Ceratops', the horncores of both genera are nevertheless indistinguishable from those of some other horned dinosaurs, including Albertaceratops and Kosmoceratops; 'Ceratops' is therefore maintained as a nomen dubium. Cladistic analysis recovers Spiclypeus as the sister taxon to the clade Vagaceratops + Kosmoceratops, and appears transitional in the morphology of its epiparietals. The discovery of Spiclypeus adds to the poorly known dinosaur fauna of the Judith River Formation, and suggests faunal turnover within the formation.